PREPARATION AND CHARACTERIZATION OF FLEXIBLE PLASTIC PACKAGING USING ACRYLIC POLYMER SOLUTION - Hussein, Seenaa Ibraheim (Malaysian Journal of Science, 2020)
In this paper , packaging plastic industrial were prepared with a flexible polymer and an additional weight ratio of nanoZrO2 .The method cast preparation was used in the preparation of samples and mechanical tests were carried out , including tear resistance , hardness, impact , tensile properties and water permeability . It was found that the improvement in mechanical properties increased weight ratio of ZrO2 due to this nano particles of the specification of the high quality mechanical, but the water permeability decreases with the increase weight ratio of ZrO2. Due to ZrO2 filled with polymer , an increase of 46% tear resistance , 14.6% hardness , 8.6% impact resistance , and 162% tensile strength (Ts) , 150 % tensile modulus (Tm) .